TRPV4 Regulates Breast Cancer Cell Extravasation, Stiffness and Actin Cortex - Wen Hsin Lee; Lee Yee Choong; Naing Naing Mon; Ssu-Yi Lu; Qingsong Lin; Brendan Pang; Benedict Yan; Sri Ram Krishna Vedula; Himanshu Singh; Tuan Zea Tan; Jean Paul Thiery; Chwee Teck Lim; et al. (2016)
Abstract Metastasis is a significant health issue. The standard mode of care is combination of chemotherapy and targeted therapeutics but the 5-year survival rate remains low. New/better drug targets that can improve outcomes of patients with metastatic disease are needed. Metastasis is a complex process, with each step conferred by a set of genetic aberrations. Mapping the molecular changes associated with metastasis improves our understanding of the etiology of this disease and contributes to the pipeline of targeted therapeutics. Here, phosphoproteomics of a xenograft-derived in vitro model comprising 4 isogenic cell lines with increasing metastatic potential implicated Transient Receptor Potential Vanilloid subtype 4 in breast cancer metastasis. TRPV4 mRNA levels in breast, gastric and ovarian cancers correlated with poor clinical outcomes, suggesting a wide role of TRPV4 in human epithelial cancers. TRPV4 was shown to be required for breast cancer cell invasion and transendothelial migration but not growth/proliferation. Knockdown of Trpv4 significantly reduced the number of metastatic nodules in mouse xenografts leaving the size unaffected. Overexpression of TRPV4 promoted breast cancer cell softness, blebbing, and actin reorganization. The findings provide new insights into the role of TRPV4 in cancer extravasation putatively by reducing cell rigidity through controlling the cytoskeleton at the cell cortex.